1991
DOI: 10.1002/j.1551-8833.1991.tb07152.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Mechanism of Inactivation of Escherichia coli B by Monochloramine

Abstract: To better understand the mode of action of monochloramine, its effect on the structural and physiological integrity of Escherichia coli B was studied. The disinfectant did not severely damage the cell envelope of the bacterium or affect nucleic acid function. Inhibition of typical protein‐associated biological activities, e.g., bacterial transport, respiration, and substrate dehydrogenation, were observed at concentrations normally used for disinfection. Differences in rates of kill and inhibition of various b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
0
4

Year Published

1992
1992
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 21 publications
5
47
0
4
Order By: Relevance
“…In these studies, monochloramine reacted rapidly with only four amino acids (cysteine, cystine, methionine, and tryptophan) and very slowly with DNA and RNA and did not severely damage the cell envelope of E. coli B. In all, this previous research supports the multiple-hit monochloramine disinfection concept whereby monochloramine reacts at several sensitive sites in bacteria before the bacteria become inactivated (18). The multiple-hit concept may explain the lag phase because the multiple reactions leading to disinfection proceed slowly.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…In these studies, monochloramine reacted rapidly with only four amino acids (cysteine, cystine, methionine, and tryptophan) and very slowly with DNA and RNA and did not severely damage the cell envelope of E. coli B. In all, this previous research supports the multiple-hit monochloramine disinfection concept whereby monochloramine reacts at several sensitive sites in bacteria before the bacteria become inactivated (18). The multiple-hit concept may explain the lag phase because the multiple reactions leading to disinfection proceed slowly.…”
Section: Resultssupporting
confidence: 72%
“…The presence of a lag phase during monochloramine disinfection is not surprising based on its proposed disinfection mechanism from studies involving Escherichia coli B (17)(18)(19). In these studies, monochloramine reacted rapidly with only four amino acids (cysteine, cystine, methionine, and tryptophan) and very slowly with DNA and RNA and did not severely damage the cell envelope of E. coli B.…”
Section: Resultsmentioning
confidence: 99%
“…It is explained by the formation of monochloramine (NH 2 Cl) in equilibrium with NCT (36,39). Because of its higher lipophilicity, NH 2 Cl penetrates and kills microorganisms more rapidly than NCT (11,36,40).…”
Section: Discussionmentioning
confidence: 99%
“…As a disinfectant, monochloramine is as effective as free chlorine for bacteria inactivation at a high dose or after prolonged contact time [32]. Jacangelo et al [33] found that at a concentration normally used for disinfection (2-20 mg/L), monochloramine did not severely affect the bacterial nucleic acid structure. The inactivation was mainly due to the inhibition of protein-associated biological processes, such as bacterial respiration, membrane transport and substrate dehydrogenation.…”
Section: Removal Through Ozonation and Chlorinationmentioning
confidence: 99%